Pelvic Rocking Dengan Birth Ball Meningkatkan Efikasi Diri dan Dilatasi Servik Ibu Bersalin - Khairunisya Khairunisya; Umi Daimah (Gorontalo Journal of Public Health, 2022)
Childbirth is an experience that requires confidence. There is a tendency to increase fear. Women's readiness and self-efficacy for pregnancy and childbirth is an issue to prevent prolonged labor. The use of a bithball can increase self-confidence and speed up the progress of labor. This study aims to determine the effect of pelvic rocking with birth ball on self-efficacy and cervical dilation at PMB Muara Enim in 2021. This study uses a quasi-experimental method with a post-test only design with a control group design. The subjects in this study were normal primiparous mothers who met the inclusion and exclusion criteria. The study sample size was 60 people who were divided into two intervention and control groups. This research instrument uses childbirth self-efficacy inventory (CBSEI). Data analysis using unpaired difference test.The results obtained at the beginning of the study there was no difference in self-efficacy and opening in the two groups. After the study, it was found that there was a significant difference in self-efficacy and progress of labor in the two groups (p value = 0.000). So it can be concluded that there is an effect of pelvic rocking with birth balls on self-efficacy and cervical dilatation in women giving birth. It is recommended for maternity mothers to practice pelvic rocking exercises while sitting on a maternity ball as a significant way to improve labor progress, as well as improve self-control.